A nanotwinned-alloy strategy enables fast sodium deposition dynamics - Guodong Zou; Jinming Wang; Yong Sun; Weihao Yang; Tingting Niu; Jinyu Li; Liqun Ren; Zhi Wei Seh; Qiuming Peng (Nature Communications)
Abstract Sodium (Na) metal batteries are considered promising solutions for next-generation electrochemical energy storage because of their low costs and high energy densities. However, the slow Na dynamics result in unfavorable Na deposition and dendrite growth, which compromise cycling performance. Here we propose a nanotwinned alloy strategy prepared by high-pressure solid solution followed by Joule-heating treatment to address sluggish Na dynamics, achieving homogeneous Na deposition. By employing cost-effective Al-Si alloys for validation, Si solubility of 10 wt.% is extended through a high-pressure solid solution, and nanotwinned-Si particles, with a volume fraction of 82.7%, are subsequently formed through Joule-heating treatment. The sodiophilic nanotwinned-Si sites exhibit a high diffusion rate, which reduces the nondimensional electrochemical Damköhler number to far below 1, shifting the diffusion-controlled deposition behavior to reaction-controlled deposition. This transition facilitates spherical Na deposition and dendrite-free growth, allowing a symmetric cell to achieve stable Na plating/stripping over 5300 h at 5 mA cm−2 with a cumulative capacity of 13.25 Ah cm−2. This strategy is also demonstrated in another CuAg system with nanotwinned Ag structures.